The OD Focus Group: A versatile tool for planned change - McLennan, Roy (School of Management Working Papers, 1992)
This paper is intended to establish the OD focus group as a versatile, rapid, and inexpensive information gathering, processing and action-taking strategy in an organizational context. It employs both an interactive and nominal group process, intended to stimulate systematic, constructive conversation with a purpose. This account, based on both experience and the literature, provides operating rules and a rationale directed towards fostering the use of the OD focus group by the manager and the consultant. The OD focus group emerges as a flexible, user-friendly, insightful alternative to both the interview and the questionnaire. Because of the shortcomings of the latter, the OD focus group is likely to come into widespread use in planned organizational change in the years ahead.